ENCOURAGING CIRCULAR ECONOMY PRACTICES IN SMALL AND MEDIUM-SIZED ENTERPRISES: THE EXAMPLE OF HOUSEHOLD WASTE UTILIZATION - Tharika, Riska; Rahmawati, Meita; Sari, Fitri Nanda; Sitepu, Christian Damar Sagara (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This community service program was set up to help people in the community who don't know much about the economic potential of controlling domestic garbage. The program was put into action in Muara Penimbung Ulu Village, Ogan Ilir Regency. It was aimed at micro, small, and medium-sized businesses, housewives, and young people. The answer included community socialization events, technical instruction on how to compost organic trash and turn inorganic waste into handicrafts, using composting equipment at home, and mentoring on how to run a business based on waste. We evaluated the program's success by how well participants understood it, made products, and engaged with the community. The results indicated that people were more aware of the environment, more involved in their communities, and able to make compost and recycled crafts. This program helps the community reduce trash, improve the quality of the environment, and create long-lasting green jobs.